Proceedings of the International Scientific Conference "Far East Con" (ISCFEC 2020) 2020
DOI: 10.2991/aebmr.k.200312.054
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Practice-Oriented Training as the Basis of University Competitiveness

Abstract: The change to practice-oriented training is caused by intensification of applied and practical character of higher education. Practice-oriented approach allows students to acquire necessary professional skills and competence, to obtain experience of organizational work, the system of theoretical knowledge, ability to work in a team and to take responsibility for the decisions made. All these correspond to Federal State Educational Standard, qualification profile of a specialist and make the university graduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Improving the relationship between theory and practice in basic professional educational programs of teacher education will enable the future teachers to use both types of knowledge for the successful implementation of labor activity at school. In addition, Prosalova and Nikolaeva (2020) have concluded that practice-oriented approach allows students to acquire necessary professional skills and competence, to obtain experience of organizational work, the system of theoretical knowledge, ability to work in a team and to take responsibility for the decisions made.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the relationship between theory and practice in basic professional educational programs of teacher education will enable the future teachers to use both types of knowledge for the successful implementation of labor activity at school. In addition, Prosalova and Nikolaeva (2020) have concluded that practice-oriented approach allows students to acquire necessary professional skills and competence, to obtain experience of organizational work, the system of theoretical knowledge, ability to work in a team and to take responsibility for the decisions made.…”
Section: Discussionmentioning
confidence: 99%
“…The latter contributes to the development of individual abilities, the creation of conditions for active, fruitful, educational, and cognitive creative activity, and provides for the creative use of organizational forms and methods. Prosalova and Nikolaeva (2020) analyzed the impact of teaching methodology, strategy, motivation, and character building on the effectiveness of training. As a result of the study, the advantages of a practice-oriented approach were revealed for each of the participants in the educational process (a higher educational institution, type of activity, and students were taken into account).…”
Section: Related Researchmentioning
confidence: 99%